2018
DOI: 10.1021/acs.langmuir.7b03719
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Surfactant Clustering at Interfaces and Its Influence on the Interfacial Tension: Atomistic Simulation of a Sodium Hexadecane–Benzene Sulfonate–Tetradecane–Water System

Abstract: The process of equilibration of the tetradecane-water interface in the presence of sodium hexadecane-benzene sulfonate is studied using intensive atomistic molecular dynamics simulations. Starting as an initial point with all of the surfactants at the interface, it is obtained that the equilibration time of the interface (several microseconds) is orders of magnitude higher than previously reported simulated times. There is strong evidence that this slow equilibration process is due to the aggregation of surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…To further elucidate the effects of polar components on IFT, we analyze the hydrogen bond density between polar compounds and water in the interfacial regions ρ HB , which is defined as where A xy is the cross-sectional area of the x–y plane (nm 2 ) and “2” appears in the denominator since there are two interfaces in the system. The interfacial region is estimated by the “90–90” criteria . The hydrogen bond is recognized when the donor–acceptor distance is less than 0.35 nm and the angle between the vectors of donor-hydrogen and hydrogen-acceptor is less than 30° .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further elucidate the effects of polar components on IFT, we analyze the hydrogen bond density between polar compounds and water in the interfacial regions ρ HB , which is defined as where A xy is the cross-sectional area of the x–y plane (nm 2 ) and “2” appears in the denominator since there are two interfaces in the system. The interfacial region is estimated by the “90–90” criteria . The hydrogen bond is recognized when the donor–acceptor distance is less than 0.35 nm and the angle between the vectors of donor-hydrogen and hydrogen-acceptor is less than 30° .…”
Section: Resultsmentioning
confidence: 99%
“…The interfacial region is estimated by the "90−90" criteria. 97 The hydrogen bond is recognized when the donor−acceptor distance is less than 0.35 nm and the angle between the vectors of donor-hydrogen and hydrogen-acceptor is less than 30°. 98 N and S in N-and S-bearing compounds only serve as acceptors, whereas the OH group in O-bearing compounds acts as both acceptor and donor.…”
Section: Resultsmentioning
confidence: 99%
“…Studying surfactants assemblies is affected by the time scales accessible to the simulations. Paredes et al 25 showed that to predict the interfacial tension for the water-tetradecane interface in the presence of sodium hexadecane benzene sulfonate surfactants, it is necessary to conduct simulations for several s. This length scale far exceeds that of most MD simulation studies reported to quantify the properties of surfactant aggregates, including those from our group.…”
Section: Possible Simulation Approaches To Study Surfactants Adsorptionmentioning
confidence: 99%
“…Studies on the molecular arrangement of surfactants at the vacuumwater interfaces [1,2] have found the formation of molecular aggregates of surfactants at the interfacial region when they have relatively high concentrations of surfactants. Recently, molecular dynamic simulations of 8-phenyl hexadecane sulfonate, located at the n-tetradecane/water interface, have reported similar aggregation of surfactants at low concentration [2]. In that work, Paredes et al concluded that the interface equilibrium time (several microseconds) is orders of magnitude greater than the obtained in other systems simulated.…”
Section: Introductionmentioning
confidence: 99%
“…In that work, Paredes et al concluded that the interface equilibrium time (several microseconds) is orders of magnitude greater than the obtained in other systems simulated. In fact, there was convincing indication that this slow equilibration process is due to surfactant aggregation at the interfacial region [2]. Therefore, the understanding of the nature of the aggregation in this type of molecules is fundamental and would have strong consequences on their simulation times.…”
Section: Introductionmentioning
confidence: 99%